REE Geochemistry of Euphrates River, Turkey - Kalender, Leyla; Aytimur, Gamze (Hindawi Ltd, 2016)
The study area is located on the Euphrates River at 38 degrees 41 degrees 32.48 '' N-38 degrees 14' 24.10 '' Nlatitude and 39 degrees 56' 4.59 '' E-39 degrees 8 degrees 13.41 '' E longitude. The Euphrates is the longest river in Western Asia. The lithological units observed from the bottom to the top are Permo-Triassic Keban Metamorphites, Late Cretaceous Komurhan Ophiolites, Upper Cretaceous Elazig Magmatic Complex, Middle Eocene Maden Complex and Kirkgec, it Formation, Upper Pliocene and Lower Eocene Seske Formation and Upper Miocene, Pliocene Karabakir and Caybagi Formations, Palu Formation, and Holocene Euphrates River sediments. The geochemical studies show that Sr-87/Sr-86 and Nd-143/Nd-144 isotopic compositions in the Euphrates River bank sediments are 0.7053, 0.7048, and 0.7057 and 0.512654, 0.512836, and 0.512775, respectively. These values indicate mixing of both carbonate-rich shallow marine sediment and felsicmafic rocks from Elazig Magmatic Complex into the stream sediments. The positive epsilon Nd(0) values (0.35, 3.9, and 2.7) are higher downstream in the studied sediments due to weathering of the mafic volcanic rocks. The chondrite, NAS, and UCC normalized patterns show that the REE compositions of the Euphrates River sediments are higher than chondrite composition but close to NAS and UCC. The river sediments in the tectonic zone and the weathered granodioritic rocks of the Elazi. g Magmatic complex affect upstream water compositions.
Keywords: Rare-Earth-Elements; Sediments; Fractionation; Evolution; Patterns; Waters; Sr; Distributions; Mobility; Elazig